2016
DOI: 10.1063/1.4967817
|View full text |Cite
|
Sign up to set email alerts
|

The physics of photon induced degradation of perovskite solar cells

Abstract: Lead-trihalide perovskite solar cells are an important photovoltaic technology. We investigate the effect of light induced degradation on perovskite solar cells. During exposure, the open-circuit voltage (Voc) of the device increases, whereas the short-circuit current (Isc) shows a decrease. The degradation can be completely recovered using thermal annealing in dark. We develop a model based on light induced generation of ions and migration of these ions inside the material to explain the changes in Isc, Voc, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…The instability of the perovskite originates from its soft nature that is based on the low interaction energy between cation and iodide ion. In addition to the decomposition of CH 3 NH 3 PbI 3 with light illumination, the photoexcited carriers could reduce the energy barrier of ion migration and thus accelerate the migration process to generate more deep‐level trap defects in the devices . Figure S8, Supporting Information, shows XPS I 3d core‐level spectra at the surface of the silver electrode in the perovskite solar cell before and after 48 h light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…The instability of the perovskite originates from its soft nature that is based on the low interaction energy between cation and iodide ion. In addition to the decomposition of CH 3 NH 3 PbI 3 with light illumination, the photoexcited carriers could reduce the energy barrier of ion migration and thus accelerate the migration process to generate more deep‐level trap defects in the devices . Figure S8, Supporting Information, shows XPS I 3d core‐level spectra at the surface of the silver electrode in the perovskite solar cell before and after 48 h light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has been successfully used to explain the origin of J-V hysteresis in HOIPs. 35,[44][45][46] We found that at (Table S1). From this, we can estimate that the Vp in our pi-n device is ~0.5 V. This value is similar to Vp that was calculated by Cameron, Peter, and coworkers for an n-i-p device using transient photovoltage measurements.…”
Section: Resultsmentioning
confidence: 99%
“…10 The stability under illumination at different temperatures was studied by Holzhey et al 11 Joshi et al studied the light-induced degradation under inert atmosphere. 12 Christians et al recently demonstrated that replacing TiO 2 with SnO 2 as an electron transport layer enables a stable operation for at least 1000 h under full spectrum irradiation. 13 Several studies demonstrated that the combination of light and oxygen is particularly harmful to the performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%